ANALISIS PENGARUH RESIKO DAN EFFISIENSI TERHADAP KINERJA BANK SYARIAH (Studi Kasus pada Bank Syariah di Indonesia pada periode 2013-2017) - Syahidan Afda; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2019)
This study aims to examine whether risk and efficiency affect the performance of Islamic banks in Indonesia. Risk is measured using the ratio of Reserve Requirement (RR), Financing to Deposit Ratio (FDR), Non Performing Finance (NPF), Capital Adequacy Ratio (CAR). Efficiency is measured using the ratio of Operational Expenses to Operating Income (BOPO). Islamic bank performance is measured using the Return on Assets (ROA) ratio. The population in this study consists of all Islamic banks that are and operate in Indonesia in the period 2013-2017. A total of 55 samples were used in this study with sample selection using the purposive sampling method. Analysis of the data used is descriptive statistics, classic assumption tests and hypothesis testing with multiple regression analysis methods tested using SPSS software. The results of this study indicate that Non Performing Finance (NPF) and Operational Expenses to Operating Income (BOPO) have a significant effect on the performance of Islamic banks, in contrast to Reserve Requirement (RR), Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR ), and Company Size that does not have a significant influence on the performance of Islamic banks.